Demographic and genetic description of Greenland's only indigenous Atlantic salmon Salmo salar population. Issue 1 (7th January 2019) - Arnekleiv, Jo V.; Davidsen, Jan G.; Sheehan, Timothy F.; Lehnert, Sarah J.; Bradbury, Ian R.; Rønning, Lars; Sjursen, Aslak D.; Kjærstad, Gaute; Lubinski, Barbara A.; Nilssen, Kjell J.
Abstract : A survey of the Kapisillit River system was conducted in 2005 and 2012 to study the only indigenous Atlantic salmon Salmo salar population in Greenland. Little is known about its characteristics or its relationship with other S. salar populations across the species range. Juvenile S. salar were captured in all stations surveyed within the lower river with the highest densities lower in the river and decreasing densities with increasing distance from the river mouth. Captured juveniles ranged from 0+ to 7+ years old and the predominant smolt age was between 4 and 6 years. Median length of 0+ and 1+ juveniles in August–September was 38.8 and 70.4 mm, respectively. The proportion of mature male parr increased from 4% for 1+ year old fish to 95% for fish greater than 2 years old. Genetic analysis using 96 single nucleotide polymorphisms (SNP) revealed a high degree of genetic similarity between collections, extremely low genetic diversity and low estimates of effective population size ( N e = 28.7; 95% CI = 19.7–42.4). Genetic comparison to range‐wide S. salar populations demonstrated that the Kapisillit River S. salar is an outgroup of the eastern Atlantic stock complex, which is consistent with the hypothesised colonisation from the east. River morphology and the absence of glacier runoff are hypothesised to be the main reasons for the relatively high river temperatures supporting this self‐sustaining population of S. salar . Given its uniqueness and persistence, this population represents an important part of range‐wide biodiversity of S. salar .